Pengaruh Efikasi Diri, Hardiness, Dan Lingkungan Belajar Terhadap Minat Belajar Pada Peserta Didik SMKN XX - Intan Septiany Simbolon; Marsofiyati Marsofiyati; Christian Wiradendi Wolor (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study was to determine the effect of Self-Efficacy, Hardiness, and Learning Environment on Academic Stress in Students of SMKN XX. The research method used is a survey method with a quantitative approach. The population in this study were students in grades X, XI, and XII of SMKN XX totaling 210 students. The sampling technique used is the probability sampling method with the Slovin formula with an accuracy of the difficulty level of 5% so that a sample of 100 students is obtained. The data analysis technique used in this study uses validation and reliability tests which are calculated using IBM SPSS (Statistical Package for Social Science) software version 24. The results of this study indicate that there is a positive and significant effect on interest in learning, there is a positive and significant effect between the effects of self-efficacy, hardiness, and learning environment together on interest in learning.